The effect of cold ambient temperature and preceding active warm-up on lactate kinetics in female cyclists and triathletes - Morrissey, M. C.; Kisiolek, J. N.; Ragland, T. J.; Willingham, B. D.; Hunt, R. L.; Hickner, R. C.; Ormsbee, M. J. (Applied Physiology, Nutrition, and Metabolism, 2019)
The aim of this study was to evaluate the effect of cold ambient temperature on lactate kinetics with and without a preceding warm-up in female cyclists/triathletes. Seven female cyclists/triathletes participated in this study. The randomized, crossover study included 3 experimental visits that comprised the following conditions: (i) thermoneutral temperature (20 °C; NEU); (ii) cold temperature (0 °C) with no active warm-up (CNWU); and (iii) cold temperature (0 °C) with 25-min active warm-up (CWU). During each condition, participants performed a lactate threshold (LT) test followed by a time to exhaustion trial at 120% of the participant`s peak power output (PPO) as determined during prior peak oxygen consumption testing. Power output at LT with CNWU was 10.2% ± 2.6% greater than with NEU, and the effect was considered very likely small (effect size (ES) = 0.59, 95%-99% likelihood). Power output at LT with CNWU was 4.2% ± 5.4% greater than with CWU; however, the effect was likely trivial (ES = 0.25, 75%-95% likelihood). At LT, there were no significant differences between interventions groups in oxygen consumption, blood lactate concentration, heart rate, or rating of perceived exertion. Time to exhaustion at 120% at PPO was 11% longer with CNWU than with CWU (ES = 0.62, respectively), and this effect was likely small. These findings suggest that power output at LT was higher in CNWU compared with NEU. Additionally, time to exhaustion at 120% of PPO was higher in CNWU compared with CWU and no different than NEU; these differences likely result in a small improvement in performance with CNWU versus CWU and NEU.